Embryotomy in the 19th Century of Central Italy. (12th August 2014) - Capasso, L.; Sciubba, M.; Hua, Q.; Levchenko, V. A.; Viciano, J.; D'Anastasio, R.; Bertuch, F.
Abstract: An enormous earthquake in L'Aquila in 2009 brought to light human bodies buried in the underground rooms of the medieval St. John the Evangelist church (Casentino, Central Italy). Among the remains, we discovered a human fetus, whose post‐cranial bones were wrapped in bandages and cranial bones were reallocated inside a sort of hood. Anthropometrical investigation revealed an age at death of 29 ± 2 weeks of pregnancy for the little mummy. Radiograph analysis of the fetus showed that the skull was dissected and disconnected from the vertebral column, and the post‐cranial bones were completely disarticulated from the axial skeleton. The body was reassembled in a way of anatomic connection at a later stage. This mummified fetus dated toad 1840 showed paleopathological evidence of a possible embryotomy and could be a rare and unquestionable case of embryotomy in archaeological context. Copyright © 2014 John Wiley & Sons, Ltd.